The Role Of Father And Self Control Against Cyberbullying In Adolescents In Yogyakarta Indonesia - Alif Muarifah, Nina Zulida Situmorang, Sri Saktiar (International Journal of Advanced Science and Technology, 2020)
This research study aims to examine the role of fathers and self-control on cyberbullying. This researchinvolved 238 students in Yogyakarta City (139 female, 99 male, the age range of 12 to 16 years old).The respondents filled out the scale of fathers’ role, self-control scale, and cyberbullying scale. Thisresearch used a quantitative correlational approach with path analysis technique. Analysis of the mainhypotheses shows that the role of father correlates very significantly with cyberbullying, both directlyand mediated by self-control. The role of fathers is directly correlated with cyberbullying with acorrelation (-0.175). This correlation value is smaller than the correlation value of the role of the fatheragainst cyberbullying mediated by self-control (-0.334). Besides, this study shows the role of fathershas a positive and very significant correlation with self-control 0.678. Self-control is negatively relatedand very significant with cyberbullying (-0.664).